The role of human resource management in facing technological disruption - Bahiroh, Eloh; Gunadi, Indra (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Technological changes in the workplace have led to profound transformations in organizational dynamics and interactions between employees and technology. This article presents an overview of the impact of technology on the workplace and the resistance management strategies implemented in dealing with these changes. This research outlines the broad impacts of technological change, from changes in work processes to organizational structure and employee well-being. In this context, employee resistance to change is a major concern, with factors such as fear, absenteeism, and perceptions of injustice influencing the level of resistance. This article also highlights the key role of human resource management (HRM) in managing resistance, emphasizing the importance of effective communication, employee engagement, and the implementation of HRM technologies that facilitate the communication process. Through a deeper understanding of these dynamics, organizations can develop more effective strategies for managing technological change and reducing employee resistance.